2015
DOI: 10.2147/copd.s85363
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of the asthma–COPD overlap syndrome – a systematic review

Abstract: Background and objectiveIn recent years, the so-called asthma–chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) has received much attention, not least because elderly individuals may present characteristics suggesting a diagnosis of both asthma and COPD. At present, ACOS is described clinically as persistent airflow limitation combined with features of both asthma and COPD. The aim of this paper is, therefore, to review the currently available literature focusing on symptoms and clinical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…13–15 However, the criteria for ACOS differs between studies, 30 as some are based on symptoms and spirometric parameters, 28,31 others on the presence of a physician’s diagnosis of both asthma and COPD, 13,32–34 and some on a mixture of these criteria. 14,35 …”
Section: Discussionmentioning
confidence: 99%
“…13–15 However, the criteria for ACOS differs between studies, 30 as some are based on symptoms and spirometric parameters, 28,31 others on the presence of a physician’s diagnosis of both asthma and COPD, 13,32–34 and some on a mixture of these criteria. 14,35 …”
Section: Discussionmentioning
confidence: 99%
“…Rhee et al36 in Korea have shown that individuals with ACOS were likely to use emergency rooms and be hospitalized for their respiratory condition compared with individuals with COPD alone. The two large systematic reviews and meta-analyses conducted on ACOS have affirmed these findings by demonstrating that patients with ACOS have greater symptomatic burden and require greater health care utilization including emergency department visits and hospitalization than individuals with COPD alone3745.…”
Section: Clinical Presentation Of Acosmentioning
confidence: 95%
“…Patients with ACOS experience more severe symptoms than those with either asthma or COPD alone, with more frequent and more severe exacerbations5 and more frequent hospitalizations 4. Patients with ACOS have been shown to be significantly younger than those with COPD, with a higher body mass index (BMI),6 and greater medical resource utilization and economic burden 7,8…”
Section: Introductionmentioning
confidence: 99%